Analisis Kebutuhan Airflow Budget Di Level Extraction Pada Tambang Bawah Tanah Di Area Deep Mill Level Zone (Dmlz) PT. Freeport Indonesia Timika Papua - Yudho Dwi Galih Cahyono; Avellyn Shinthya Sari; Billi Hanok Wambukomo (PROMINE, 2021)
Freeport Indonesia (PTFI) is a mining company that is an affiliate of Freeport-McMoran Copper & Gold Inc. (FCX) and PT Indonesia Asahan Aluminum (Persero) (Inalum). As of 2019, the Government of Indonesia has taken over 51.23% of shares (41.23% Inalum, 10% Regional Government of Papua). The research methods used in this activity are observational and comparative methods. In analyzing the calculation factors of design budget criteria. The data obtained will be used to compare direct field observation data with monthly report data from the company and equalize it with the air standard for underground mine ventilation based on the Decree of the Minister of Mines and Energy No. 1827 K / 30 / MEM / 2018. Calculation of airflow budget for the equipment used In the calculation and processing of airflow budget data is the R1600 LHD loader, the results of the Utilization Factor for 1 year are obtained by regulation of the Government of PT. Freeport itself uses in accordance with the regulations, namely 0.067 multiplied by 208Kw from the R 1600 LHD tool, obtaining an average 0.302 Maximum 0.482 Minimum 0.033 With a total air supply into the DMLZ mine of 1338 m3 / s, this is very sufficient from the results of the total air demand based on the airflow buget design in accordance where is 1095.6 m3 / s. In underground mining, DMLZ is in accordance with the regulation of the Decree of the Minister of Energy and Mineral Resources of the Republic of Indonesia Number 1827 K / 30 / MEM / 2018